2018
DOI: 10.1371/journal.pone.0190940
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of boost timing in murine irradiated sporozoite prime-boost vaccines

Abstract: Vaccination with radiation-attenuated sporozoites has been shown to induce CD8+ T cell-mediated protection against pre-erythrocytic stages of malaria. Empirical evidence suggests that successive inoculations often improve the efficacy of this type of vaccines. An initial dose (prime) triggers a specific cellular response, and subsequent inoculations (boost) amplify this response to create a robust CD8+ T cell memory. In this work we propose a model to analyze the effect of T cell dynamics on the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
1
10
0
1
Order By: Relevance
“…Greater protective efficacy associated with stronger immune responses after a wider prime-boost interval have been seen with other vaccines such as those for influenza, Ebola virus disease, and malaria. 16 , 17 , 18 The findings presented here for the ChAdOx1 nCoV-19 vaccine are consistent with policy recommendations in different countries to use dose intervals of 4–12 weeks for this vaccine.…”
Section: Discussionsupporting
confidence: 86%
“…Greater protective efficacy associated with stronger immune responses after a wider prime-boost interval have been seen with other vaccines such as those for influenza, Ebola virus disease, and malaria. 16 , 17 , 18 The findings presented here for the ChAdOx1 nCoV-19 vaccine are consistent with policy recommendations in different countries to use dose intervals of 4–12 weeks for this vaccine.…”
Section: Discussionsupporting
confidence: 86%
“…Although most likely this is the case, the direction of the effect of this extension is unpredictable. Within a similar time frame, the effect of boost timing on the CD8+ T-cell memory response was shown to be dependent on the antigen itself, the antigen dose and actual exposure time [ 26 , 27 ], leading to enhancement of clonal expansion or to contraction [ 26 ]. This has not been investigated for this model and antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these antigen-dependent parameters is especially important to predict the influence of variations in the timing of immunizations on the generation of protective T cell responses. Using mathematical modeling, a previous study on the interaction of WSV dose and the timing of booster injections recently reported that boosting during the late phase of clonal contraction maximized memory T cell formation when using lower RAS doses, while a single inoculation was more effective in this respect when using a higher dose ( 54 ). However, this study only considered administration of a single boost not later than 7 days post priming and did not take into account the impact on interacting organ-specific or late memory responses.…”
Section: Discussionmentioning
confidence: 99%